Pengembangan Sistem Kearsipan Berbasis Web di Perusahaan PT Teknoreka Inovasi Nusantara - Nala Rusydal Khakim; Nurkhamid (Department of Electronics and Informatics Engineering Education, 2025)
The aim of this research is twofold: (1) To develop a document archiving information system at PT Teknoreka Inovasi Nusantara. (2) To ensure quality by testing the archiving information system at PT Teknoreka Inovasi Nusantara using functional suitability testing for feasibility and usability testing for user-friendliness in utilizing the information system. The method employed in this research is Research and Development (R&D). The development method used is the waterfall model, consisting of 5 stages: Communication, followed by Planning, Modeling, Construction, and finally Deployment. There were 2 expert respondents for functional suitability testing and 15 respondents for functional usability testing. Data collection methods used include observation, interviews, and questionnaires. The outcome of this research is a web-based information system named Tekdok, designed to manage incoming and outgoing correspondence and facilitate archivists in archiving at PT Teknoreka Inovasi Nusantara. The results of the functional suitability aspect testing yielded a score of 100%, indicating that all functions operate well and are